The associations of adolescent problematic internet use with parenting: A meta-analysis - Lukavská, Kateřina; Hrabec, Ondřej; Lukavský, Jiří; Demetrovics, Zsolt; Király, Orsolya (Addictive behaviors, 2022)
Problematic internet use (PIU) has adverse effects on adolescent health. Parenting may play an important role in the prevention of this condition, but the associations between PIU and parental behavior are unknown. This meta-analysis examined the associations between adolescent PIU and general and media-specific parenting. Studies were obtained using searches in scientific databases and using references identified from bibliographies. Searches covered English written journal articles, master's theses, and doctoral dissertations from the year each database started until April 2022. Studies were included if they (a) measured PIU, (b) measured parenting, (c) used data obtained from children or adolescents, and (d) reported a valid analysis. Two coders decided whether each study met the required criteria. Data were pooled using a random effects model. We found weak negative associations between PIU and general parenting, namely, warmth (r = -0.17, [-0.13, -0.20], k = 24; N = 58401), control (r = -0.10, [-0.01, -0.18], k = 10, N = 12199), and authoritative parenting (r = -0.12, [-0.02, -0.21], k = 8, N = 5431), but the associations between PIU and media-specific parenting, namely, active mediation (r = -0.02, [-0.07, 0.02], k = 11, N = 30545) and restrictive mediation (r = 0.01, [-0.10, 0.11], k = 16, N = 36997), were non-significant. In older adolescents, the association between restrictive mediation and PIU was significant but positive. Media parenting has only weak association with PIU and thus restrictions should be used cautiously, especially in older adolescents. Additional prospective studies on parenting and specific PIU activities are needed.
Keywords: Problematic Internet Use; návykové chování; Gaming Disorder; Problematic Smartphone Use; Humans; chování mladistvých; dítě; používání internetu; Child; lidé; Parental Mediation; internet; Internet; Adolescent Behavior; Parenting; Adolescent; Parental Control; Parental Warmth; Internet Use; rodičovství; prospektivní studie; Behavior, Addictive; mladiství; Prospective Studies